Proposta de uma sequência de atividades do Desmos para o ensino de função afim - FARIAS, Ewerton Fanuel da Silva (2024)
The present text shows a sequence of Desmos activities for teaching affine function, with an emphasis on offering students a robust knowledge of the principles linked to this content, while improving their skills to solve problems and strengthen their ability to think critically. The general concepts of this functions are exposed, and then the activities in ascending order of knowledge requirements, with most of them interactive, providing for, what we think is, more meaningful learning than traditional methods; for the simple fact of grouping in a small space, different topics of the subject, and contemplating skills and abilities contained in the BNCC for teaching mathematics.